Effect of the light emitting diodes intensity and photoperiod in the optimization of the Spirulina (Arthrospira) biomass production - Vásquez-Villalobos, V. (2017)
Biomass (ф) production from Spirulina sp. batch cultures was optimized in laboratory scale photobioreactors (LPB) of 0.2 L, by the effect of X1: intensity of light emitting diodes (LEDs) and X2: photoperiod, between 1.25-41.7 klux and 12/12-24/0 hours of light/dark (L/D) respectively using a central composite rotational design (CCRD) and response surface methodology (RSM). The hydraulic characteristics and ф value from Spirulina batch cultures were also evaluated in a closed-loop channel photobioreactor open to the atmosphere (PB-CLOA) by the effect of the lighting LED of 8.3±1.9 klux and photoperiod of 12/12 and 24/0 h L/D. Two optimal zones of ф in LPB were identified, both with a 21.5 klux LED intensity and photoperiod relationship of 12/2 and 24/0 h L/D, with values of 1.65 and 1.62 ф respectively. The mathematical model which indicated the optimal zones was of 2nd order, which had a high significance (p = 0.000396 < 0.05) achieving a predictive value of R2 = 0.92. In the PB-CLOA, the cultivation of Spirulina sp. with photoperiod of 12/12 h L/D, showed a ф value of 0.72, a more rapid adaptation of λ = 4.62 h, a higher specific growth rate of μmax=0.033 h-1 and reduced time energy consumption of 74.05 h; compared to culture developed with photoperiod 24/0 h L/D. The PB-CLOA hydraulic parameters were: operation volume 2.5 L, flow velocity 0.26 m/s, numbers of Reynolds (Re) 15488, Froude (Fr) 0.60 and Vedernikov (Ved) 0.90.